BIOGRAFI SYEKH H. MUKHTAR MUDA NASUTION SEBAGAI TOKOH PENDIDIKAN ISLAM DI KECAMATAN BARUMUN KABUPATEN PADANG LAWAS 1921-2009 - Rustalena, Rustalena; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: Sheikh H. Mukhtar Muda Nasution with his first name is Marahadam Nasution he is a scholar who persistently strives to Islamic eduction in sub-distric Barumun distric Padang Lawas. In order to fulfill his desire to deepen the science of religion he also studied in the holy land of Mecca for 4 years. Besides studying he also won the trust to teach at madrasah Nahdatul Ulama Sibuhuan which is now renamed madrasah Tsanawiyah Aek Hayuara in Sibuhuan for 9 years. This the beginning of his journey in advancing Islamis religious education many things he did to realize these ideals among which he built several educational institutional. The purpose of this research is to 1). know the life Syekh H. Mukhtar Muda Nasution, 2). the role of Syekh H. Mukhtar Muda Nasution, 3). the teaching method used by Syekh H. Mukhtar Muda Nasution, 4). the work of Syekh H. Mukhtar Muda Nasution. The method used is quantitative, this research is field research to obtain data through interview and documentation. The results show that Syekh H. Mukhtar Muda Nasution has a big role in advancing the Islamis education in sub-district Barumun district Padang Lawas.Key Words: Figure In Islamic Education